Effect of oral CoQ10 supplementation along with precooling strategy on cellular response to oxidative stress in elite swimmers. Issue 8 (30th July 2018) - Emami, Ali; Bazargani-Gilani, Behnaz
Abstract : High intensity and prolonged swimming trainings in a hot and humid environment lead to stimulated and increased production of reactive oxygen and nitrogen species (RONS). Abstract : High intensity and prolonged swimming trainings in a hot and humid environment lead to stimulated and increased production of reactive oxygen and nitrogen species (RONS). In this study, we examined the effects of 14-day coenzyme Q10 (CoQ10 ) supplementation and precooling strategy on the serum levels of NADPH-oxidase (NOX), hydrogen peroxide (H2 O2 ), lactic acid (LA), creatine kinase (CK), 8-isoprostane (8-iso PGF2α ), 8-hydroxy-2-deoxyguanosine (8-OHdG), aspartate aminotransferase (AST), protein carbonyls (PC), alanine aminotransferase (ALT), and gamma-glutamyl transferase (GGT) in adolescent elite swimmers. Thirty-six healthy boys (mean ± SD: age = 17 ± 1 years) were randomly assigned into 4 groups: supplementation, precooling, supplementation with precooling, and control. Blood sampling was carried out pre- and post- (two stages) administration of CoQ10 along with precooling with heavy trainings. ANCOVA and repeated measurement tests with the Bonferroni post-hoc test were used for statistical analysis of data ( α = 0.05). No significant difference was found among the groups for serum levels of H2 O2, NADPH-oxidase, CK, LA, 8-OHdG, 8-iso PGF2α, PC, AST, ALT, and GGT at pre-sampling ( P > 0.05). The precooling group showed significant increase in index levels compared to the supplementation and supplementation with precooling groups in post sampling (stages 1 and 2), respectively ( P < 0.05). Oral administration of CoQ10 inhibited adverse changes in oxidative stress and muscle and liver damage indices in the competition phase of swimming. No desired effect of the precooling strategy was found on the serum levels of NADPH-oxidase, CK, LA, 8-iso PGF2α, 8-OHdG, H2 O2, AST, PC, ALT, and GGT.